Psychosis, dissociation and psychosis : evolving perspectives on severe psychopathology.: evolving perspectives on severe psychopathology. (2018) - Moskowitz, Andrew; Dorahy, Martin J, 1971-; Schäfer, Ingo, 1971-
No abstract available